Access to Sustainability in Conservation-Restoration Practices - Pinheiro, Catarina (2024)
Cultural heritage faces significant threats from environmental challenges and unchecked development. Sustainability has made its way into the field, and there is a growing interest in seeing it thrive. The particular field of the conservation and restoration of tangible movable cultural heritage is also being improved by new concepts and treatment options more aligned with environmental standards. This article investigates the integration of sustainability into the conservation and restoration of this specific cultural heritage by leveraging the SCOPUS and BCIN databases to examine the evolution of scientific content on the topic over the past 24 years. Key trends in research include assessing greener practices in conservation and education and guidance for the promotion of sustainable practices. These themes are also championed by organizations and initiatives that disseminate this message to conservation professionals through effective and less formal communication strategies. The findings emphasize the critical value of bridging the gap between scientific research and practical application, advocating for accessible resources and collaborative efforts to advance sustainable conservation practices.